Training For Processing Household Waste Into Eco-Enzyme (Liquid of Million Benefits) Based on Eco-Community in Supporting Increasing Family Income in Padang City - Vevi Sunarti; Jalius Jalius; Wisroni Wisroni; Reza Gusmanti (Universitas Negeri Padang, 2021)
Family welfare in West Sumatra has begun to falter due to the coronavirus (Covid-19) with the reduction of workers, resulting in a decrease in family income. Not a few families experience limitations and powerlessness in meeting basic needs, this makes people look for solutions by staying at home but still being able to meet family needs. The training on processing household waste into eco-enzymes based on eco-community is carried out as one solution to the problems faced by the community, which aims to make household waste that has been thrown away into eco-enzymes as a liquid (a million benefits) based on eco-community so that waste can be used and even economically valuable so that it becomes family income and city problems can also be resolved. The training for productive age housewives who do not work to utilize household waste into eco-enzymes that are of the sale value and can be used at home as a multi-purpose liquid and to develop the life skills of housewives so that they can take advantage of their free time and can help the husband in meeting the economic needs of the family. This training has an impact in 1) increasing family income despite working from home; 2) being able to take advantage of the free time of housewives by the skill of processing waste; 3) the formation of an eco-community as a society that cares about the environment and makes waste with economic value; 4) reduce waste as a problem in the city of Padang.